EP.FRI.758 Management of Small Bowel Obstruction: A Retrospective Audit. (28th October 2021) - Baggaley, Alice; Clements, Caterina; Tudyka, Vera
Abstract: Aims: How does management of small bowel obstruction (SBO) at a district general hospital in London compare with current recommendations from the BMJ Best Practice algorithm and the National Audit for Small Bowel Obstruction (NASBO)? Methods: This retrospective audit captured patients admitted with SBO over a four-month period. Two authors searched the general surgery admission lists and extracted hospital numbers. A total of 59 patients were identified initially but nineteen of these patients were subsequently excluded, leaving 40 to be analysed. Inclusion criteria involved age 18 or over and SBO proven on imaging. Results: The majority of the obstructions were secondary to adhesions (65%), with 10% due to hernia, 7% due to inflammatory bowel disease and 5% due cancer. All but one patient underwent computed tomography (CT) and in 90% of cases this was performed within 12 hours of initial assessment. For those who underwent a period of conservative management, 64% received a water-soluble study. Seven patients had immediate surgery within 12 hours of admission, and 5 patients proceeded to surgery after failed conservative management. Of the patients who failed conservative management, only one was operated on after the 72 hours. Conclusions: Access to CT was excellent, as was time to theatre when the decision was made for immediate surgery. There was not a difference in access to imaging or theatre given the time or day of the week. Use of water-soluble studies in conservative management could be increased and the time to this study could be formalised.